Measurement and interpretation of moments in inclusive semileptonic decays B[bar]→Xcℓ−ν[bar] - Aubert, Bernard; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We present results for the moments of observed spectra in inclusive semileptonic B-meson decays to charm hadrons B[bar]→Xcℓ−ν[bar]. Moments of the hadronic-mass and the combined mass-and-energy spectra for different minimum electron or muon momenta between 0.8 and 1.9 GeV/c are obtained from a sample of 232×106 Υ(4S)→BB[bar] events, collected with the BABAR detector at the PEP-II asymmetric-energy B-meson factory at SLAC. We also present a reevaluation of the moments of electron-energy spectra and partial decay fractions B(B[bar]→Xce−ν[bar]) for minimum electron momenta between 0.6 and 1.5 GeV/c based on a sample of 51×106 Υ(4S)→BB[bar] events. The measurements are used for the extraction of the total decay fraction, the Cabibbo-Kobayashi-Maskawa (CKM) matrix element |Vcb|, the quark masses mb and mc, and four heavy-quark QCD parameters in the framework of a Heavy-Quark Expansion (HQE). We find B(B[bar]→Xcℓ−ν[bar])=(10.64±0.17±0.06)% and |Vcb|=(42.05±0.45±0.70)×10−3.
Gesehen am 28.11.2022
Im Titel steht der Buchstabe B sowie der Buchstabe v mit einem Oberstrich
Im Titel ist der Buchstabe c tiefgestellt
Im Titel ist der Minuszeichen hochgestellt